Energía eléctrica limpia mediante celdas fotovoltáicas para la implementación en un sector de la Facultad de Sistemas de la Universidad Técnica de Ambato - Salcedo, Carlos (2011)
The purpose of this project aimsto implement a self-sustainingphotovoltaic system at the Facultad de Ingeniería en Sistemas, Electrónica e Indutrial of the Universidad Técnica de Ambato on the basis of a geostationary analysisand characterization ofthe amount of radiationabsorbed and disseminatedthrough the atmosphere at the specífic point established on the basis of mathematical calculations to determine SolarIrradiation MeanValúes for all months of the year depending on latitude andlongitude on geostationary axis, the equator and the meridian of Greenwich. The project issequential and permanent character, as the panels are implemented, and should be gradually enabling students in the operation and management of equipment and elements of the project to update the information, inciudingbasedata and software for continuous recording and monitoring.The photovoltaic system consists of three solar panels and 100W, a controller of 40A, a inverter of 2500W, three lamps 70A, four batteries i05Ah, cables, and the support structure. Additionally, with the donatlon of seven solar panels by theEcuadorian Institute of Friendship - Chínese.